The possibility of human placenta extract in the treatment of symptoms genitourinary syndrome in postmenopausal women - M R Orazov; M B Khamoshina; T N Bebneva; S R Policarpova (IP Berlin A.V., 2017)
Article is devoted an actual problem of modern gynecology - correction of the symptoms genitourinary syndrome (GUS), which has important medical and social importance. In addition to traditional hormone therapy, modern medicine has a broad range of metabolic substances, antioxidants and reparants to treat women with clinical manifestations of GUS. In this prospective study were 62 women aged up to 60 years in postmenopausal women with clinical symptoms of GUS, for the comprehensive treatment which the metabolic therapy was used the Melsmon (human placenta extract for subcutaneous injection).The results of the study demonstrated high clinical efficiency of the use of this therapy for relief of symptoms of GUS that improve the quality of life for women of postmenopausal age.